Pengaruh Kepemimpinan Transformasional, Kompetensi Pegawai dan Budaya Organisasi Terhadap Kinerja Pegawai melalui Motivasi Kerja - Welhelmus Daniel Dami; Simon Sia Niha; Agapitus H. Kaluge; M. E. Perseveranda; Anggraeny Paridy (Univiversitas Dr. Djar Wattiheluw, 2024)
This research aims to comprehend Employee Performance, Work Motivation, Transformational Leadership, Employee Competency, and Organizational Culture at the Office of the Chief Port and Port Authority Class III Kupang, as well as to examine the influence of variables related to Work Motivation as a mediator and employee performance as a dependent variable. This research is quantitative in nature, utilizing both primary and secondary data, and employing descriptive and inferential statistical analyses. The results indicate that Transformational Leadership, Employee Competency, and Organizational Culture significantly influence employee work motivation; Work Motivation significantly affects employee performance; and Work Motivation mediates the influence of Transformational Leadership, Employee Competency, and Organizational Culture on Employee Performance at the Office of the Chief Port Class III and Port Authority Kupang